Antioxidant and antidiabetic activities of a polyphenol rich extract obtained from Abelmoschus esculentus (okra) seeds using optimized conditions in microwave-assisted extraction (MAE) - Woumbo, Cerile Ypolyte; Kuate, Dieudonné; Metue Tamo, Danielle Gaelle; Womeni, Hilaire Macaire (Frontiers in Nutrition, 2022)
Functional foods have gain more popularity in recent decades. They are exploited for their bioactive compounds like polyphenols, highly demanded either in cosmetic, pharmaceutical and nutraceutical industries. But extractive techniques and conditions used up to recently are almost obsolete and then need to be optimized for high efficiency. This study aimed at evaluating the antidiabetic potential of an optimized extract of Abelmoschus esculentus (okra) seeds. Determination of the optimal conditions for extraction of polyphenolic compounds from okra seeds was made using the Microwave Assisted Extraction (MAE). A Face Center Composite Design (FCCD) was used for optimization. Solvent/dry matter ratio, wavelength and time were the factors considered while the response studied was the polyphenolic content. The extract obtained at optimal conditions was characterized using Tin Layer Chromatography (TLC) and Fourier Transform Infra-Red (FTIR) spectroscopy, then tested for it antioxidant, alpha amylase inhibitory and antidiabetic activities. RSM permitted us to determine the optimal conditions for phenols extraction as: microwave power 330 W, with a solvent ratio of 97.04/1 ml/g for 9.5 min of extraction time. The optimized extract showed a phenolic content up to 86.37±1.13 mg GAE/g and contained quercetin and catechin as revealed by the TLC. Functional groups characteristic of polyphenols were identified on FTIR spectra and the extract exhibited good in vitro antioxidant capacities with DPPH radical scavenging capacity and FRAP. An IC50 of 3.99 ±0.15 µg/ml was obtained with the DPPH scavenging test. Alpha amylase inhibitory assay revealed that the optimized okra extract behaved as a non-competitive inhibitor of porcine pancreatic amylase with an IC50 of 484.17±2.33µg/ml. Antidiabetic activity of the extract was observed in streptozotocin induced diabetic males Wistar’s rats, as shown by the fasting blood glucose levels, food intakes, weight changes and serum lipid profile among others.